Efektivitas Media Pembelajaran Power Point Terhadap Hasil Belajar Siswa - Ahmad Muflih Saefuddin (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
Textbooks are an important part of the learning process. Using appropriate teaching resources can improve student learning outcomes. One of the most commonly used teaching tools is Power Point. The purpose of this study was to analyze the effectiveness of the Power Point teaching tool on student learning outcomes using a qualitative literature approach. This study uses secondary data in the form of educational journals to discuss the effectiveness of the Power Point teaching tool on student learning outcomes. Research shows that Power Point teaching tools are effective in improving student learning outcomes. Several factors confirm this: Power Point teaching aids engage students and make learning interactive. PowerPoint tutorials can present learning materials more clearly and interestingly. PowerPoint teaching aids help students understand course material. Therefore, using Power Point teaching materials can be an alternative to improve students' academic performance. However, it should be noted that the Power Point teaching tool must be used accurately and creatively to achieve the best results.